KEBEBASAN BERAGAMA SEBAGAI HAK KONSTITUSI DI INDONESIA - Pieter Radjawane (Faculty of Law, Universitas Pattimura, 2014)
Human Rights in general is defined as every human rights acquired since he was born that apply universally. In Indonesia, religious freedom is a part of many human rights are constitutionally stipulated in the Constitution of the Republic of Indonesia in particular in Article 28A through Article 28J. Which is then more specifically regulated in Law Number 39 Year 1999 on Human Rights, and Law No. 12 of 2005 on the Ratification of the International Covenant On Civil Rights and Politics (International Covenant on Civil and Political Rights). Karenya each of Indonesia's population is given the freedom of religion but in practice these freedoms must remain within the limits stipulated in legislation